Del manejo tradicional al manejo orgánico del olivar: aplicaciones prácticas del conocimiento histórico - González de Molina Navarro, Manuel (2014)
The mere substitution of chemical inputs for organic usually guide the redesign of farms that want to convert to organic production. This often leads to significant errors in the configuration of the new agro-ecosystem and promoting a management quite close to the conventional one instead of a truly sustainable management. This error stems from the lack of historical depth when the dynamics of agro-ecosystems is analyzed for organic conversion. This article argues that the study of agricultural systems in the past may be useful for the design of sustainable systems, providing an eminently practical or applied function to the Agrarian History. The experiences of management and functioning of agro-ecosystems in the past, especially when using renewable energy and fertilizers of animal origin, can provide useful knowledge to improve the sustainability of organic farming. The comparative study of traditional and modern forms of management of olive carried out in this article have that goal. To do this, we describe the organization and functioning of preindustrial olive agro-ecosystems in a case study, Baena, representative of the Andalusian olive grove. Then predominant management from a few decades ago and is typical of industrial agriculture is characterized. From the comparison of the two forms of management, traditional and industrial, raises several recommendations that should be taken into account for the design of organic olive groves from an agro-ecological point of view.